SWEAR WORDS IN KPOPMINTON TREND AMONG BADMINTON LOVERS IN TWITTER: A STUDY ON LANGUAGE AND GENDER - Ainia Arum Novitasari; Sailal Arimi (Universitas Cokroaminoto Palopo, 2024)
The phenomenon of the Kpopminton trend among badminton lovers on Twitter lately is very fascinating to discuss. This phenomenon has drawn a lot of criticism from badminton lovers because it combines the worlds of different things, namely K-pop and badminton. The aim of this research is to investigate the forms and references of swearing, as well as differences in gender forms of swearing in Kpopminton trends that occur on Twitter among badminton fans. This research uses a descriptive approach with qualitative methods. Data collection was carried out using the notetaking and listening method. The results of this research show that comments on the Kpopminton trend among badminton fans on Twitter contain a lexicon of swear words, where the male gender is wider and more varied. Swearing is classified based on its morphological and syntactic lingual form, as well as its linguistic form. Referents of swear words used by men are conditions, animals, activities, objects, and body parts. Meanwhile, women use more polite referents, although they still tend to be rude, namely referents related to objects and animals. Lastly, men tend to use more swear words than women with a harsher choice of curse words as can be seen from the level. The level of swear words shows that in terms of extreme levels the curses are spoken by men. At high levels, it is spoken by both men and women. Meanwhile, at the standard level it is spoken by women.